Characterization of the complete mitochondrial genome of the moss, Myurella julacea (Schwägr.) Schimp. (Bryidae, Theliaceae) - Jin-Woo Jung; Yeong-Deok Han; Young-Jun Yoon (Mitochondrial DNA. Part B. Resources, 2021)
The present study reports the complete mitochondrial genome of Myurella julacea (Schwägr.) Schimp. (GenBank accession number MT850126); the genome size was 104,979 bp. The gene arrangement was found to be similar to that in other bryophytes, and the genome consisted of 40 protein-coding genes (PCGs), 3 ribosomal RNAs (rRNAs), and 24 transfer RNAs (tRNAs). The phylogenic relationship was analyzed by construction of a phylogenetic tree based on the mitogenome of M. julacea and 25 other bryophytes publicly available in GenBank. The complete mitogenome of M. julacea is expected to provide insights into the evolution of species belonging to the order Hypnales.